Multiple myeloma increases nerve growth factor and other pain-related markers through interactions with the bone microenvironment - Sam W. Z. Olechnowicz; Megan M. Weivoda; Seint T. Lwin; Szi K. Leung; Sarah Gooding; Guido Nador; Muhammed Kassim Javaid; Karthik Ramasamy; Srinivasa R. Rao; James R. Edwards; Claire M. Edwards (Scientific Reports, 2019)
Abstract Interactions between multiple myeloma (MM) and bone marrow (BM) are well documented to support tumour growth, yet the cellular mechanisms underlying pain in MM are poorly understood. We have used in vivo murine models of MM to show significant induction of nerve growth factor (NGF) by the tumour-bearing bone microenvironment, alongside other known pain-related characteristics such as spinal glial cell activation and reduced locomotion. NGF was not expressed by MM cells, yet bone stromal cells such as osteoblasts expressed and upregulated NGF when cultured with MM cells, or MM-related factors such as TNF-α. Adiponectin is a known MM-suppressive BM-derived factor, and we show that TNF-α-mediated NGF induction is suppressed by adiponectin-directed therapeutics such as AdipoRON and L-4F, as well as NF-κB signalling inhibitor BMS-345541. Our study reveals a further mechanism by which cellular interactions within the tumour-bone microenvironment contribute to disease, by promoting pain-related properties, and suggests a novel direction for analgesic development.